Uniportal Endoscopic Lumbar Interbody Fusion - Ralf Wagner; Monika Haefner (Neurospine, 2020)
The cause of radiculopathy is the compression of the nerve root which can be secondary to sliding of the vertebra and reduced disc height. In some patients, decompression alone does not resolve this problem. We describe the uniportal endoscopic transforaminal lumbar interbody fusion technique. Full-endocopic foraminotomy and discectomy are followed by cage implementation and percutaneous instrumentation. The goal of this surgical method is decompression of nerve roots, segment stabilization, disc height, and sagittal alignment restoration. Uniportal endoscopic facet sparing transforaminal transkambin lumbar interbody fusion is a good surgical option to treat degenerative disc disease, mechanical instability, and spondylolisthesis. This method shows favourable clinical outcomes in selected patients.